Measurement of lactate removal magnitude during swim performances at maximal aerobic speed - Schnitzler, C.; Ernwein, V.; Chollet, D. (First international symposium sciences and practices in swimming, 2006)
We investigated a method to assess the magnitude of lactate removal (%Hlar) as a function of expertise, the distance swum and improvement in performance. Seventeen competitors and 16 recreational swimmers performed a 400-m freestyle swim at maximal speed. Lactate was measured 1 (Hla1'), 3 (Hla3') and 5 (Hla5') minutes post-trial. Lactate removal was calculated assuming the relationship: %Hlar=[(Hla3'-Hla5')/Hlap]*100, where Hlap is the peak lactate value. The competitors then performed 100-, 200- and 300-m trials at the speed of the 400-m. In addition, their %Hlar values from retraining to the end of the season were compared. %Hlar was higher in the experts than in the recreational swimmers (8.6±7.2% vs. 1.8±8.5%; p < 0.05). %Hlar increased gradually in the competitors with the increase in the distance swum (-1.9±13.2, 4,7±5.5, and 8.5±10 for 100-, 200-, and 300-m, respectively; p < 0.05). No difference was found in %Hlar between the beginning and end of the season despite improved performances. %Hlar seems to be an interesting tool to assess training Status from maximal aerobic speed. However, this method failed to detect changes linked with improved performances.